Mogamulizumab versus investigator’s choice of chemotherapy regimen in relapsed/refractory adult T-cell leukemia/lymphoma - Phillips, Adrienne A. (2019)
Mogamulizumab, a humanized defucosylated anti-C-C chemokine receptor 4 monoclonal antibody, has been approved in Japan for the treatment of C-C chemokine receptor 4-positive adult T-cell leukemia/lymphoma (ATL). This phase II study evaluated efficacy and safety of mogamulizumab in ATL patients with acute, lymphoma, and chronic subtypes with relapsed/refractory, aggressive disease in the US, Europe, and Latin America. With stratification by subtype, patients were randomized 2:1 to intravenous mogamulizumab 1.0 mg/kg once weekly for 4 weeks and biweekly thereafter (n=47) or investigator's choice of chemotherapy (n=24). The primary end point was confirmed overall response rate (cORR) confirmed on a subsequent assessment at 8 weeks by blinded independent review. ORR was 11% (95%CI: 4-23%) and 0% (95%CI: 0-14%) in the mogamulizumab and chemotherapy arms, respectively. Best response was 28% and 8% in the respective arms. The observed hazard ratio for progression-free survival was 0.71 (95%CI: 0.41-1.21) and, after post hoc adjustment for performance status imbalance, 0.57 (95%CI: 0.337-0.983). The most frequent treatment-related adverse (grade ≥3) events with mogamulizumab were infusion-related reaction and thrombocytopenia (each 9%). Relapsed/refractory ATL is an aggressive, poor prognosis disease with a high unmet need. Investigator's choice chemotherapy did not result in tumor response in this trial; however, mogamulizumab treatment resulted in 11% cORR, with a tolerable safety profile.